An Integrative Framework for Patriotic Values in Strengthening Community Resilience to Disasters from a Public Health Perspective - Saputra, Dwi Arwandi Yogi; Savitri, Pritha Maya; Zahrah, Siti Nuriyatus; Syafitri, Nurul Mawwadah; Banjarnahorq, Riri Oktavani (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
Indonesia, as a country with a high level of disaster vulnerability, faces significant challenges in maintaining public health resilience. Community resilience is a crucial aspect in mitigating the impact of morbidity, mortality, and psychosocial distress resulting from disasters. This study aims to develop an integrative framework for implementing the values of national defence in strengthening disaster-based community resilience from a public health perspective. The method employed was a qualitative approach through a literature review of scientific articles from 2021 to 2025. The findings indicate that national defence values such as social solidarity, mutual aid, and collective awareness act as social capital that strengthens community adaptive capacity, enhances preparedness, and supports the resilience of the health system. This study produced an integrative framework comprising core values, implementation mechanisms, community health capacity, and outcomes in the form of public health resilience.